2007
DOI: 10.1016/j.yqres.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironmental proxy records from Lake Hovsgol, Mongolia, and a synthesis of Holocene climate change in the Lake Baikal watershed

Abstract: Here we discuss paleoenvironmental evolution in the Baikal region during the Holocene using new records of aquatic (diatom) and terrestrial vegetation changes from Hovsgol, Mongolia's largest and deepest lake. We reconcile previous contradictory Baikal timescales by constraining reservoir corrections of AMS dates on bulk sedimentary organic carbon. Synthesis of the Holocene records in the Baikal watershed reveals a northward progression in landscape/vegetation changes and an anti-phase behavior of diatom and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 40 publications
3
100
0
1
Order By: Relevance
“…These proxies at both sites are consistent with BioSi/diatom responses in indicating a prolonged interval of high primary production and accumulation of organic matter (OM) in the lake. By analogy with Holocene (TOC 1-3% dry sediment weight, Prokopenko et al, 1999Prokopenko et al, , 2007 and the last interglacial (TOC 1.5-2%, Prokopenko and Williams, 2003), sustained high OM accumulation during MIS 11 (TOC 1-2%, Figs. 3, 4) may be interpreted as an indication of high lake productivity characteristic of "full-scale" interglacial conditions, not unlike those during MIS 1 and MIS 5e intervals.…”
Section: Productivity Proxy Records Of Mis 11 Interglacial In Lake Bamentioning
confidence: 93%
See 1 more Smart Citation
“…These proxies at both sites are consistent with BioSi/diatom responses in indicating a prolonged interval of high primary production and accumulation of organic matter (OM) in the lake. By analogy with Holocene (TOC 1-3% dry sediment weight, Prokopenko et al, 1999Prokopenko et al, , 2007 and the last interglacial (TOC 1.5-2%, Prokopenko and Williams, 2003), sustained high OM accumulation during MIS 11 (TOC 1-2%, Figs. 3, 4) may be interpreted as an indication of high lake productivity characteristic of "full-scale" interglacial conditions, not unlike those during MIS 1 and MIS 5e intervals.…”
Section: Productivity Proxy Records Of Mis 11 Interglacial In Lake Bamentioning
confidence: 93%
“…Previously, the close temporal relationship between BioSi/diatom and arboreal pollen proxies for warm regional climate has been established for the radiocarbondated Holocene interval (e.g. Prokopenko et al, 2007) and for the paleointensity-dated last interglacial interval, as seen from the comparison of diatom (Rioual and Mackay, 2005) and pollen records. For older interglacial and interstadial intervals, the apparent durations (thicknesses) agree in pollen and BioSi/diatom records as well (Table 1).…”
Section: The Apparent Duration Of the Mis 11 In The Lake Baikal Recordmentioning
confidence: 95%
“…3A). This effect is well known and has been described for the large lakes in different parts of the world (e.g., Moreton et al, 2004;Prokopenko et al, 2007;Watanabe et al, 2009;Zhou et al, 2015).…”
Section: Coring and Age-depth Modelmentioning
confidence: 74%
“…Evidences and suggestions supporting our hypothesis are provided by studies on the sediment from Lake Hovsgol. Prokopenko et al (2007) showed that the early Holocene diatom/biogenic silica (bioSi) peaks correlated with the humidity maximum (Fig. 6f) reconstructed by the pollen fossil analyses and from predictions of GCMs (Bush, 2005).…”
Section: Continental Erosion/weathering Changes In Central Asia Durinmentioning
confidence: 85%
“…6f) reconstructed by the pollen fossil analyses and from predictions of GCMs (Bush, 2005). Based on these observations, Prokopenko et al (2007) regarded that the early Holocene increase of diatom abundance in Lake Hovsgol was caused by increased nutrient supply with high precipitation and surface runoff. The early Holocene diatom/bioSi peaks correspond to the increased Br contents in core HDP-06 (Fig.…”
Section: Continental Erosion/weathering Changes In Central Asia Durinmentioning
confidence: 99%